Proteoforms of transthyretin - candidate biomarkers in diagnosis of obstructive sleep - Torres, VM (2017)
Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder which is characterized by recurrent occurrence of partial or complete closure of the upper airway during sleep, despite ongoing efforts to breathe. The majority of patients with OSA remain undiagnosed since most of them only come to the attention of a clinician when they complain of daytime sleepiness or when their bed partners report loud snoring or witnessed apnea episodes.Epidemiological studies have indicated that OSA affects 6–13% of the adult population. OSA is multifactorial disease, also considered as metabolic syndrome, which diagnosis in early stages is challenging thus often remain undiagnosed. Recently was found connection between transthyretin (TTR) protein modifications present in human plasma samples and appearance of sleep apnea syndrome1,2 . Mass Spectrometric Immunoassay (MSIA) was successfully applied previously on identification of and quantification of TTR variants present in human serum3. We took advantage on this powerful method to investigate possible modifications of TTR proteoforms in patients with OSAS.